2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626862
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of feature extraction techniques on event-related potentials for detection of attention-deficit/hyperactivity disorder

Abstract: Event-related potentials (ERPs) are one of the most informative and dynamic methods of monitoring cognitive processes, which are widely used in clinical research to deal a variety of psychiatric and neurological disorders as attention-deficit/hyperactivity disorder (ADHD). This work proposes an extraction and selection methodology for discriminating between normal and pathological patients with ADHD by using ERPs. Three different sets of features (morphological, wavelets, and nonlinear based) are analyzed, loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…• Biomedical signals. Large part of the studies have focused on electroencephalogram (EEG) [42,30,32,41,43,31] and event-related potentials (ERP) [26,12]. More innovative (and much more expensive) techniques such as magnetoencephalography (MEG) have been also applied [19].…”
Section: Objective Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Biomedical signals. Large part of the studies have focused on electroencephalogram (EEG) [42,30,32,41,43,31] and event-related potentials (ERP) [26,12]. More innovative (and much more expensive) techniques such as magnetoencephalography (MEG) have been also applied [19].…”
Section: Objective Methodsmentioning
confidence: 99%
“…[35] Table 6 Separability analysis and classification performance obtained after application of previously reported actigraphy-based methods (6 most meaningful indices for each kind of method when significant results-p < 0.05-were obtained for more than 6 features, only significant results otherwise with SD reveals higher variability in the control group associated to transitions between "mid" and "high" activity levels-P(21) and P (12). These results should be carefully interpreted, since the higher dynamic range of activity in the ADHD group can lead to lower transition occurrences.…”
Section: Statisticsmentioning
confidence: 99%
“…ERP is considered as one of the most effective methods to monitor cognitive processes. Relevant researchers believed that ERP can be used to screen various pathological nerve disorders and achieve higher screening accuracy, such as ADHD and ASD (Castro-Cabrera et al, 2010). Meanwhile, some studies have shown that individuals with ASD have a poor perception of facial expression of others (Kiyoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, there have been attempts to extract measures that correlate with ADHD symptoms from body worn physiological sensors. Some of these objective tools are based on continuous performance tests (CPTs) [ 8 ] and electroencephalogram (EEG) [ 9 ]. EEG and CPT testing can be costly to administer, requiring expensive equipment and specialized personnel, especially in the case of EEG [ 10 ].…”
Section: Introductionmentioning
confidence: 99%